Enhancing H+ conduction through glycolic acid-doped alginate-PVA based biopolymer electrolytes - N. M., Ghazali; Aoki, K.; Nagao, Y.; Ahmad Salihin, Samsudin (Elsevier Ltd, 2024)
This study investigates the development of a biopolymer blend electrolyte composed of alginate and poly (vinyl alcohol) (PVA), doped with glycolic acid (GA) to enhance H+ conductivity. The addition of GA significantly impacts the biopolymer blend's physicochemical properties and ionic conduction performance. Fourier transform infrared (FTIR) spectroscopy verified the intricate interactions and hydrogen bonding between the alginate-PVA matrix and GA. The addition of GA was shown to increase the amorphous phase, as observed through X-ray diffraction (XRD) and scanning electron microscopy (SEM) analysis. This increase in the amorphous phase was found to enhance the thermal stability. Impedance analysis demonstrated a significant increase in ionic conductivity from approximately ∼10⁻⁸ S cm⁻1 for the undoped blend to 3.45 × 10⁻⁵ S cm⁻1 with 30 wt% GA (sample GA-30). The enhanced H+ conduction behaviour was consistent across various temperatures, adhering to the Arrhenius rule. These findings suggest that the alginate-PVA-GA system is a promising candidate for efficient proton transport applications.